Frontline Science: Anti‐PD‐L1 protects against infection with common bacterial pathogens after burn injury. Issue 1 (21st December 2017) - Patil, Naeem K.; Luan, Liming; Bohannon, Julia K.; Hernandez, Antonio; Guo, Yin; Sherwood, Edward R.
Abstract: Burn patients are susceptible to infections due, in part, to immune dysfunction. Upregulation of programmed death‐1 (PD‐1) receptor on T cells and programmed cell death ligand‐1 (PD‐L1) on myeloid cells contribute to immune dysfunction in nonburn‐related sepsis. We hypothesized that PD‐1/PDL1 interactions contribute to immune dysfunction after burn injury. To determine the impact of burn injury and infection on PD‐L1, PD‐1 and costimulatory receptor expression by leukocytes and its relationship to T cell functions. The efficacy of anti‐PD‐L1 antibody was evaluated in a clinically relevant mouse model of burn injury and bacterial infection. Mice underwent 35% scald burn followed by Pseudomonas aeruginosa or Staphylococcus aureus infection on day 4 postburn. Anti‐PD‐L1 was administered on day 3 postburn. Numbers and phenotype of leukocytes, plasma cytokine concentrations, bacterial clearance, organ injury, and survival were assessed. Burn injury and infection with P. aeruginosa caused a significant upregulation of PD‐L1 on myeloid cells, along with a decrease in T cell numbers and function, significant multiorgan injury, and decreased survival. Treatment with anti‐PD‐L1 antibody improved bacterial clearance, reduced organ injury, and enhanced survival during Pseudomonas burn wound infection. Furthermore, anti‐PD‐L1 effectively protected against multiorgan injury, and improved bacterial clearance and survival following systemic S. aureus infection after burn injury. Blockade of PD‐1/PD‐L1 interactions might represent a viable treatment to improve outcomes among critically ill burn‐injured subjects and increased leukocyte PD‐L1 expression could serve as a valuable biomarker to select appropriate patients for such treatment.